Perceptions about learning in stroke through a mHealth application in Brazil: A case study (Research, Society and Development, 2022)
Stroke - Cerebral Vascular Accident, occurs when a blood vessel in the brain is ruptured or blocked, interrupting blood flow and oxygen (Meschia et al., 2014), being the 2nd leading cause of death in the world, (Brasil & Ministry of Health, 2020), (George, 2020), (SOBRAC - Brazilian Society of Cardiac Arrhythmias, n.d.), (Adams et al., 2008), (Ducroquet et al., 2013). Due to the accessibility of cell phones in Brazil, it is possible to propose innovative applications for stroke education. The objective of this study is to present insights about learning and using the EduAVC application. Methodology - It is an applied research, with a qualitative approach, with a descriptive objective, Minayo (Cecília de Souza Minayo & Ferreira Deslandes Otávio Cruz Neto, 2002) and Creswell (Creswell, 2014), in the case study modality, (Yin K, 2010). It consisted in the development of the EduAVC application for Android, in Portuguese, for Google Play stores. It has scientific information, animated videos and illustrations about the disease, being a mHealth (C et al., 2018), (PP et al., 2019), (BF et al., 2020). We created an instrument to collect the perceptions of research participants in relation to the 37 items, in 4 sections that aimed to measure learning, ease of use, organization of information and usefulness of the application, being approved by the Research Ethics Committee (CEP) in Health Sciences, from the University of Brasília, with CAAE: 40507820.4.0000.0030. Results - There was a predominance of “Very Satisfied” and “Satisfied” users such as EduAVC, with perceptions that indicated a majority that have a graduate degree, having witnessed a CVA in the family. Conclusions - The application registered acceptability of use by the participants and some effectiveness in education about the disease, and may be suitable for learning about stroke in Brazil and in emerging countries according to other mHealth proposals - mHealth, (Nimmolrat et al., 2021), (Morris et al., 2017).